Optimization Of Carbon-S-Glass Fiber Epoxy Resin Composites With Varied Carbon Content And Fiber Orientation For Improved Beam Bumper Energy Absorption Through Analytical Approach - Haymanot Saketa (ASTU, 2023)
This Msc Thesis Focuses On The Redesign And Optimization Of The Bumper Beam For The Lifan520. The Objective Is To Demonstrate An Innovative Advancement In Composite Science By Developing A Hybrid Material Made Of Carbon-S-Glass Fiber Epoxy Resin, Replacing The Previous Steel Beam. The Aim Is To Achieve The Ideal Balance Of Strength, Rigidity, And Weight Through A Laminate Structure With A Unidirectional Fiber Arrangement. The Optimization Procedure Involves Adjusting The Percentages Of Carbon Fiber And S-Glass Fiber In The Composite Material. The Fiber-To-Matrix Ratio Is Carefully Balanced At 60% Fiber And 40%Matrix. The Evaluation Process Includes Analyzing Different Carbon Fiber Content Ranges (5%,15%, 25%, 30%, 35%, And 40%) And Assessing Key Characteristics Such As Internal Energy, Deformation, Equivalent Stress, And Directional Acceleration. The Greys Relational Analysis Technique Is Employed To Evaluate The Composite's Performance Under Various Scenarios. The Optimization Procedure Reveals That The Composition With 5% Carbon Content Stands Out Prominently And Performs Exceptionally Well Achieving The Top Spot. This Result Emphasizes The Importance Of Finding The Right Balance Between Structural Stability And Weight Savings. Furthermore, An Investigation Into The Influence Of Fiber Orientation Is Conducted. Unidirectional Fiber Alignment At 0 Degrees Consistently Holds The Top Position, DemonstratingIts Remarkable Suitability For Projected Loading Circumstances. The 22.5-Degree Orientation Follows Closely, Confirming Its Effectiveness In Various Applications. Additionally, A Multidirectional Configuration With The Coordinates (0, 90, 0, 90, 0) Degrees Achieves An Honorable Third Place, Indicating The Potential Advantages Of Multiple Fiber Orientations. Based On The Findings, It Is Recommended To Use A Composite Material With 25% Carbon Content For The Bumper Beam Of The Lifan 520. The Unidirectional Fiber Alignment At 0 DegreesIs Suggested As The Optimal Orientation For Achieving The Desired Performance Under Projected Loading Conditions. However, Considering The Potential Benefits, A Multidirectional Configuration With The Specified Coordinates May Also Be Considered For Certain Applications. The Analysis Of The Selected Material Was Conducted Using Software Such As Solidworks, Ansys Spaceclaim, Ansys21r2, Ansyscompositepreppost, And Ls-Dyna. These Tools Facilitated The Assessment Of The Material's Properties And Performance. This Msc Thesis Contributes Crucial Insights To The Field Of Composite Material Engineering And Introduces A Paradigm Shift In Automotive Material Science. The Discoveries Made Significantly Advance Our Understanding Of The Intricate Interactions Between Material Composition, Orientation, And Performance Outcomes. This Research Lays The Foundation For Future Advancements In Vehicle Safety Engineering
Keywords: Varied Carbon, Grey Relation Analysis, Hybrid, ACP, C5, FEA, Fiber Orient